Evaluating the integration methods of the higher education system in Mozambique - Miguel, Lucas Lavo António Jimo; Andissene, Andissene Américo Thodo; Gomane, Manuel Cochole P. (Frontiers in Education, 2025)
The forms of integration and articulation in tertiary education are debated globally, including studies that discuss higher education’s expansion, differentiation, diversity, and fragmentation. This review evaluates integration forms by examining selected Mozambican higher education literature and databases from 1962 to 2021. Research on higher education (HE) in Mozambique aids in assessing trends and processes of expansion, fragmentation, differentiation, and diversity. These processes are described using data from the Ministry of Science and Technology of Mozambique regarding 53 public and private universities. Statistical analyses using Excel are based on integrated data of enrollments, new admissions, and graduations to deduce the performance of isomorphism through differentiation, diversity, and fragmentation. The expansion and fragmentation of HE in Mozambique are represented by the total number of students enrolled in both public and private systems. Results indicate a slight difference in new admissions between public and private systems, while more graduations were registered in the public system compared to the private system. The comparative analysis reveals no significant differences at a 5% confidence level between new admissions and graduated students, reflecting the intensification of fragmentation within the parent institutions. Additionally, no evidence was found supporting differentiation and diversity practices in public and private institutions. The identified expansion and fragmentation processes highlight the need for decentralization to counterbalance the concentration of resources and higher education activities outside of Maputo. Although differentiation and diversity practices are absent in Mozambique’s higher education system, they could enhance educational quality and yield high-quality graduate outcomes, research, and community outreach activities. While the findings pertain specifically to the HE system in Mozambique, they provide important insights into the dynamic processes of expansion, fragmentation, differentiation, and diversity in the region.